Spot and Futures Prices and the Law of One Price - Protopapadakis, Aris; Stoll, Hans R. (Journal of Finance, 1983)
The law of one price (LOP) is tested for narrowly defined commodities traded in futures markets in different countries during the period 1973–80. Although the LOP holds as an average tendency for most of the commodities, there are instances of large riskless arbitrage returns (before transactions costs). Deviations from the LOP tend to be commodity specific rather than due to a common external factor and they tend to be smaller the longer the maturity of the futures contract.